2018
DOI: 10.1021/acsnano.7b07583
|View full text |Cite
|
Sign up to set email alerts
|

Endosomal Size and Membrane Leakiness Influence Proton Sponge-Based Rupture of Endosomal Vesicles

Abstract: In gene therapy, endosomal escape represents a major bottleneck since nanoparticles often remain entrapped inside endosomes and are trafficked toward the lysosomes for degradation. A detailed understanding of the endosomal barrier would be beneficial for developing rational strategies to improve transfection and endosomal escape. By visualizing individual endosomal escape events in live cells, we obtain insight into mechanistic factors that influence proton sponge-based endosomal escape. In a comparative study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
151
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(157 citation statements)
references
References 56 publications
5
151
1
Order By: Relevance
“…25 Other studies indicate that the actual mechanism could be much more complex than the classical proton sponge effect and may depend on fusion with the endosomal membrane and additional factors, such as the endosome size, membrane leakiness, late endosome formation, Rab7A localization on the surface of endosomes, and activation of mTORC1 for downstream signaling for protein synthesis. 26,27 Materials Used for Non-viral mRNA Delivery Ionizable Lipids. One well-studied class of non-viral mRNA delivery agents includes the cationic or ionizable lipids and lipid-like materials.…”
Section: Materials For Mrna Delivery Structural Aspects Of Materials Dmentioning
confidence: 99%
“…25 Other studies indicate that the actual mechanism could be much more complex than the classical proton sponge effect and may depend on fusion with the endosomal membrane and additional factors, such as the endosome size, membrane leakiness, late endosome formation, Rab7A localization on the surface of endosomes, and activation of mTORC1 for downstream signaling for protein synthesis. 26,27 Materials Used for Non-viral mRNA Delivery Ionizable Lipids. One well-studied class of non-viral mRNA delivery agents includes the cationic or ionizable lipids and lipid-like materials.…”
Section: Materials For Mrna Delivery Structural Aspects Of Materials Dmentioning
confidence: 99%
“…[ 64 ] Recently, a report indicated that both endosomal size and membrane leakiness resulting from a difference in cell lines affected the proton sponge‐based endosomal rupture, providing important clues toward further improvement of this escape strategy. [ 65 ] The major concerns for the use of polycationic agents are toxicity‐induced acute inflammation, hemolysis, cell necrosis, apoptosis, [ 66 ] and low cytosol delivery, which result from the strong interaction between the polycationic agent and cell membranes. In addition, polycationic agents also have high nondegradability and suffer from low dissociation of the cargo from the complex in the cells due to robust interactions between the cargo and the polycation.…”
Section: Cytosolic Delivery Via Endosomal Escapementioning
confidence: 99%
“…Viral vectors typically yield high transduction efficiencies, but their use is expensive, labor-intensive, and associated with significant safety issues [17,18]. While lipid-based and polymer-based nanoparticles can be safer alternatives, efficient transfection is often hindered by poor uptake, e.g., in blood and immune cells [14], limited endosomal escape [19,20], and delayed unpacking of the cargo molecules from the carriers in the cytosol [21]. In addition, these synthetic carriers can typically only be used with specific cargo molecules (e.g., nucleic acids) and cell types [22].…”
Section: Introductionmentioning
confidence: 99%